A questionnaire-based survey on the epidemiological and clinical characteristics of SARS-CoV-2 infection in patients with chronic HBV infection and HIV infection - Lu Chen; Chao Cai; Si-Jie Zheng; Liang Hong; Hui Zhao; Fei-Fei Su; Ming-Qin Lu (Frontiers in Public Health)
Background and aimsTraditional observational studies have yielded inconsistent findings regarding the association between COVID-19 and HBV/HIV infections, as well as the protective effects of antiviral therapy against severe COVID-19. This study aimed to investigate the potential links between the current use of antiviral therapy and the rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and symptoms of infection in patients with SARS-CoV-2 and HBV/HIV.MethodsUsing a questionnaire-based survey, we recorded whether participants had been infected with SARS-CoV-2, and the symptoms and severity of COVID-19 after the illness.ResultsAmong 756 participants, chi-square tests showed a higher incidence of COVID-19 in the HBV infection group (75.6%, p = 0.047) and the HIV infection group (77.6%, p = 0.036). These two groups exhibited fewer symptoms than the control group (p < 0.001). The differences in the prevalence of most symptoms were also significant.ConclusionOur findings suggest that patients with HBV or HIV infection have a higher risk of contracting SARS-CoV-2 than the general population; however, antiviral treatment relieves the symptoms of COVID-19.